Communicative Approach in Psycholinguistic Analysis in Arabic Learning - Mahmudah, Uswatun; Triyana (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This psycholinguistic study has two characters, namely psycho and linguistic which discusses the behavior of children in language. The research uses a literature study method that comes from relevant literature sources. The results of the study focused on the application of learning Arabic through a communicative approach without eliminating the psycholinguistic system. In both formal and informal learning processes, the psycholinguistic process works to acquire language knowledge through learning. So that this interdisciplinary can lead educators to understand the processes that occur within each student that is faced when they try to understand and provide understanding. Materials in language learning are presented in class. The objectives of this study include students being able to understand Arabic easily, especially in a communicative approach to the ability to speak Arabic both as a whole and students being able to understand theories from psycholinguistic experts in Arabic learning, then linked with a communicative approach with the aim that students are able to communicate properly and appropriately using Arabic.